Nitrogen-cycling tracing methods : Case studies at cold-climate mine sites in northern Sweden - Nilsson, Lino (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2018)
High nitrogen effluents from mine sites is an environmental issue which has received relatively little attention historically. In recent years a number of studies have showed the environmental effects of high nitrogen discharge to natural water bodies, which include local eutrophication, high risk of acute reducing conditions and changed species composition in the receiving waters. Apart from the direct environmental effects of high nitrogen discharge some forms of nitrogen can be directly toxic- ammonia and nitric gas for instance, and some can be indirectly toxic, for instance nitrate which causes methemoglobinemia in infants if ingested. This thesis shows how the developed nitrogen tracing methods can be applied in complex water transport systems such as in a mining environment. Two main study sites were used in this thesis, the LKAB iron mine at Kiruna and the Aitik copper mine at Gallivare operated by Boliden Mineral AB. The nitrogen tracing methods used in this study are stable isotope analysis, combined nitrogen and oxygen isotope analysis, source partitioning using linear combination of sources, numerical analysis using kinetic nitrogen reaction rates, numerical model verification using stable nitrogen isotopes, and Bayesian statistical models to estimate nitrogen concentrations. The study also demonstrates an experimental method of reducing nitrogen concentrations in the mining pond at the LKAB Kiruna site. The nitrogen reducing method was tested in a small scale mesocosm experiment at the Kiruna site in northern Sweden, where a nitrogen reduction rate of around 0.25 - 0.5% total nitrate per day could be achieved. The nitrogen treatment method consists of fertilising the pond system with small amounts of bioavailable phosphorus. Phosphorus is generally the limiting factor for primary production and in the studied mining systems which have high nitrogen concentrations the phosphorus is assimilated into organic matter almost immediately after fertilisation. The phosphorus is assimilated into phytoplankton ...